Legal regulation of labor of specialists in the field of physical education and sports in Ukraine - Саннікова, Марина (Slobozhanskyi Herald of Science and Sport, 2019)
Marina Sannikova Purpose: to identify areas for improving the legal regulation of labor of specialists in the field of physical education and sports in Ukraine. Material & Methods: in this study, a methodological approach was used, according to which the legal regulation of labor of specialists in the field of physical culture and sports in Ukraine was considered from the point of view of the interaction of systems of different orders. Theoretical analysis and systematization of literary sources on the topic of the study made it possible to find out the problem field of the legal regulation of labor of specialists in the field of physical education and sports in Ukraine. The analysis of documentary materials made it possible to characterize the system of legal regulation of labor of specialists in the field of physical education and sports. The application of the system analysis method made it possible to understand the logic of the deployment of the entire system of labor relations at the national and world levels, to penetrate deeply into the content and industry specifics of labor relations, to analyze in general the general trends. Methods of mathematical statistics allowed us to determine the dynamics of indicators of staffing in the field of physical education and sports in Ukraine over the past 10 years. Results: the system of legal regulation of labor of specialists in the field of physical culture and sports is described, which includes the norms of domestic labor legislation, international legal acts on the protection of labor rights, as well as industry legislative and regulatory and program documents in the field of physical culture and sports. It was found that the number of full-time employees over the past 10 years has decreased by 8,3%, in particular, due to a decrease in the number of employees of higher educational institutions, sports facilities, sports trainers, trainers, teachers and sports teachers. Conclusion: the need for improving the legal regulation of labor of specialists in the field of physical culture and sports in Ukraine in the following areas has been clarified: the creation of a unified system of certification of fitness trainers and other fitness personnel, fixed at the state level; determination of common principles for the legal regulation of labor of professional athletes; monitoring the economic feasibility of training specialists of certain specialties in the field of physical education and sports by universities.